Науково-технологічні основи виготовлення деталей та складання виробів, зміцнюваних мікродуговим оксидуванням алюмінієвого шару - Роп'як, Любомир Ярославович (Івано-Франківський національний технічний університет нафти і газу, 2018)
Дисертація на здобуття наукового ступеня доктора технічних наук за спеціальністю 05.02.08 – технологія машинобудування. – Національний технічний університет "Харківський політехнічний інститут". – Харків, 2018. У дисертаційній роботі вирішена актуальна науково-технічна проблема в об-ласті технології машинобудування: розроблено теоретичні основи та технологічні засоби для підвищення ресурсу роботи нафтогазового обладнання шляхом мікродугового оксидування поверхневого алюмінієвого шару деталей машин. Досліджено напружений стан двошарового покриття під довільно орієнтованим локальним навантаженням, розроблено методику раціонального проектування шаруватого покриття за критеріями міцності покриття та підкладки. Запропоновано модель армування субстрату для підвищення несучої здатності покриття. Розраховано напруження в циліндричній деталі з двошаровим покриттям. Розроблено груповий технологічний процес формування композиційних покриттів комплексним методом із використанням мікродугового оксидування алюмінієвого шару на компактному та напиленому алюмінії. Обґрунтовано вибір алюмінієвих сплавів, сталей та технологій формування заготовок. Розроблено обладнання для мікродугового оксидування, для електродугового напилення покриттів із суцільних дротів та порошків, модернізовано установку для віброелектроіскрового легування. Розроблено методики визначення залишкових напружень в покриттях, електрохімічних вимірювань та корозійні випробовувань і випробовувань на зношування. Обгрунтовано технологічні параметрів процесів відцентрового армування та електродугового напилення заготовок. Оптимізовано технологічні параметри процесу мікродугового оксидування в проточному електроліті для забезпечення показників якості поверхні та точності форми деталей. Вивчено структуру і фазовий склад, фізико-механічні властивості та шорсткість оксидного покриття. Вивчено особливості складання клемових з'єднаннь з неповним охопленням вала. Розроблено варіант теорії цангової гайки з підпружиненими пелюстками. Досліджено складальні напруження в елементах робочого колеса відцентрового вентилятора "диск − конічна оболонка". Запропоновано конструкцію складеного плунжера насоса із різьбовим з'єднанням із клейовим прошарком. Розроблено методику розрахунку припусків на механічну обробку деталей з оксидними покриттями. Оптимізовано режими різання під час алмазного шліфування. Проведено стендові випробовування зміцнених деталей. Запропоновано схему регенерації та утилізації відпрацьованого електроліту.

A thesis submitted to the degree of Grand Doctor of Philosophy in the Technical Sciences, major in 05.02.08 specialty − technology of mechanical engineering. National Technical University "Kharkiv Polytechnic Institute". − Kharkiv, 2018. The actual scientific and technical problem of the mechanical engineering technology field was solved: the theoretical bases and technological means for oil and gas equipment resource increasing by the plasma electrolytic oxidation of an aluminum layer were developed. The ways of layered coating bearing capacity increasing, formed by the plasma electrolytic oxidation of an aluminum layer, were grounded. The schemes of layered coatings have been developed. The stress-strain state of a two-layer coating under for an arbitrarily oriented local load is studied. The method of rational design of a two-layer coating for local load is developed. The influence of the oxide layer thickness on the resistance of the ceramic-aluminum coating to inculcation is studied. A model of substrate reinforcement – an aluminum base with particles of aluminum oxide – is proposed. An estimation of the oxide coating bearing capacity reinforced layer thickness was carried out and the increase of the bearing capacity of the oxide coating was determined, as well as the robustness of the two-layer aluminum-aluminum oxide coating for bending with the twist of the cylindrical part was estimated. The group technological process of composite coating formation by a complex method with the use of plasma electrolytic oxidation of an aluminum layer has been developed. Studied material selection – aluminum alloys and steels and technologies of forming of blanks – is grounded. Strengthening technologies and equipment for plasma electrolytic oxidation of compact aluminum and aluminum coatings in electrolyte have been developed. An installation for spray coating of composite coatings by an arc method has been developed from the material of continuous wires and powders, which are introduced from the feeder. An installation for vibroelectric doping of the substrate before coating was modernized. Studying methods of coating properties, which allow to determine the level of residual stresses in coatings, to con-duct electrochemical measurements and corrosion tests and tests on hydro- and gas-abrasive deterioration of parts with oxide coatings are developed. The plasma electrolytic oxidation technological parameter influence on the ac-curacy and quality of part surfaces is experimentally studied. The technological parameters of the plasma electrolytic oxidation process in the flowing electrolyte are optimized to ensure the quality of the surface and the accuracy of the shape of the cylindrical parts. The structure and phase composition of the oxide layer formed by the plasma electrolytic oxidation have been studied. Empirical dependencies were obtained for determining the surface roughness after diamond polishing of the oxide coating. The physical and mechanical properties of the oxide coating formed by the plasma electrolytic oxidation, the residual stresses in them, corrosion properties and wear resistance of the formed oxide layer are determined. Electrochemical method determines the level of admissive stresses in parts with coatings. The assembly of components from parts reinforced with the plasma electrolytic oxidation has been studied. The wheel assembling peculiarities of axial fans with clutch joints with a nut are studied. The method of designing a threaded connection with a collar nut is developed. The assembling stresses in the elements of the working wheel of the centrifugal fan – disk – conical shell have been studied. The design of the composite plunger of the pump is proposed: a steel shaft – a working cylinder, which strengthens the plasma electrolytic oxidation of the surface layer. The connection of the steel shaft to the working cylinder is carried out using a threaded connection with the adhesive layer. The method of calculating allowances for mechanical processing of parts with oxide coatings is developed. The cutting modes of round diamond grinding of the oxide coating layer are optimized. The bench testing of parts strengthened by the method of the plasma electrolytic oxidation: protective shaft of shafts of centrifugal pumps, piston rod piston pumps, two-way pumps, compressor pistons. The analysis of harmful factors that arise during the process of the plasma electrolytic oxidation is carried out and the scheme of purification, regeneration and recycling of spent electrolyte is proposed.
Scientific and technological bases of part manufacturing and product assembling, strengthened by plasma electrolytic oxidation of an aluminum layer
Keywords: технологічний процес; мікродугове оксидування; електродугове напилення; покриття; шорсткість поверхні; точність обробки; дисертації; technological process; micro arc oxidation; electric arc spraying; coating; surface roughness; precision of processing; 621.92:621.793